A mineralogical and geochemical study of seven meteorites from Malawi, Namibia and Lesotho - Lombard, Annegret (University of the Free State, 2010)
Seven meteorites from Malawi, Namibia and Lesotho were studied using optical microscopy, scanning electron microscopy with energy dispersive X-ray spectrometry and electron microprobe analysis of mineral phases. Induced coupled plasma spectrometry and X-ray fluorescence techniques were used to obtain chemical information. The Thuathe meteorite from Lesotho is a H4 ordinary chondrite according to major element chemistry and mineralogy. The shock features were classified as S2/3 and the weathering grade as W0. It contains Sb sulphides, which had not been previously reported in any chondritic meteorite. Berthierite and stibnite was observed under the SEM and confirmed by electron microprobe analyses. The chondrite normalised REE pattern is relatively flat with no significant LREE/HREE variation. Very slight enrichment of Ta and U compared to H-group chondrites are noted. In this study the Machinga meteorite from Malawi is classified as an E6 ordinary chondrite according to major element chemistry and mineralogy, and the shock features were classified as S4, moderately shocked. Previously it had been classified as an L6 chondrite (Graham et al, 1984 and Koeberl et al, 1990). The rare earth element pattern is relatively flat with slight LREE/HREE variation from the norm. Slight enrichment of W, Pb and U is noted. The Balaka meteorite from Malawi is a L6 ordinary chondrite that is weakly shocked (S2). These classifications were done with major element chemistry as well as the mineralogy of the meteorite. The rare earth element pattern is flat with nearly no variation between LREE and HREE. The normalised trace element diagram mirrors the trends of the trace element diagram of the L-group chondrites with respect to ordinary chondrites. The Chisenga meteorite from Malawi is an IIIAB medium octahedrite according to chemistry and the bandwidth of kamacite (~1.5 mm) and taenite. Kamacite is the dominant Fe/Ni phase and Widmanstätten texture is prominent. The unreported specimens from Asab in Namibia prove to be L6 ordinary chondrites according to major element chemistry and mineralogy. The shock features are classified as moderately shocked (S4) and the weathering grade is W2. The rare earth element spectrum for the sample 1 from Asab shows enrichment of LREE. Enrichment of Ba, Sr, Th and U is shown in this sample. Sample 2 from Asab shows slight La enrichment compared to L-group chondrites. Enrichment in Ba, Sb, Sr and U is shown in the chondrite normalised trace element diagram. Sample 3 from Asab displays a flat chondrite normalised REE pattern with nearly no variation between LREE and HREE. Chemical variation in these meteorite samples in the chondrite normalised trace element diagram shows enrichment of Ba, Sb and Sr. The general trends of the diagrams are similar indicating that the three unknown specimens are of the same fall.

Sewe meteoriete van Malawi, Namibië en Lesotho is bestudeer met behulp van optiese mikroskopie, skandeer elektron mikroskopie met energiedispersie X-straal spektrometrie en elektrone mikrosonde vir mineral fase analises. Induktief gekoppelde plasma spektrometrie en X-straal fluoressensie tegnieke is gebruik om chemiese inligting in te win vir die geochemiese interpretasie van die meteoriete. Die Thuathe meteoriet van Lesotho is ‘n H4 gewone chondriet soos bepaal met hoofelement chemise samestelling en mineralogy. Die skok-eienskappe is as S2/3 geklassifiseer en the ververings grad as W0. Dit bevat Sb sulfiedes, wat nooit voorheen beskryf is in enige chondritiese meteoriete nie. Berthieriet en stibniet is met behulp van die SEM opgespoor en met behulp van die elektrone mikrosonde geanaliseer. Die chondriet genormaliseerde SAE patroon is relatief plat met geen merkbare variasie in LSAE en HSAE. Effense verryking van Ta en U in vergelyking met H-groep chondriete kom voor. In hierdie studie is die Machinga meteoriet van Malawi geklassifiseer as ‘n E6 gewone chondriet met matige skok (S4), na aanleiding van hoofelement chemise samestelling en minerlogie. Vorige outeurs het dit as ‘n L6 chondriet geklassifiseer (Graham et al, 1984 en Koeberl et al, 1990). Die raar aard element patron is relatief plat met effense variasie van die LSAE/HSAE. Effense verryking van W, Pb en U is teenwoordig. Die Balaka meteorite van Malwi is ‘n L6 gewone chondriet met swak skok eienskappe (S2). Hierdie klassifikasies is met behulp van hoofelement chemiese samestelling asook mineralogie verkry. Die seldsame aard element patron is plat met feitlik geen variasie tussen die LSAE en HSAE. Die genormaliseerse spoorelement diagram vir die Balaka meteorite is ‘n spieëlbeeld van die van L-groep chondriete. Die Chisenga meteoriet van Malawi is ‘n tipe IIIAB medium oktahedriet na aanleiding van chemise samestelling en die bandwydte van kamasiet (~1.5 mm) en taeniet. Kamasiet is die dominante Fe/Ni fase en Widmanstätten tekstuur is prominent. ix Die drie onbekende voorbeelde vanaf Asab is L6 gewone chondriete na aanleiding van hoofelement chemise samestelling en mineralogie. Die skok-klassifikasie vir hierdie meteoriete is matig (S4) en die verwerings grad is W2. Die seldsame aard element patron vir monster 1 van Asab is verryk in LSAE. Ba, Sr, Th en U is verryk in hierdie monster. Monster 2 van Asab is effens verryk in La asook Ba, Sb, Sr en U. Die seldsame aard element patroon vir Monster 3 van Asab is plat met geen variasie tussen LSAE en HSAE. Ba, Sb en Sr is verryk in hierdie monster. Die algemene tendens van die diagramme is baie eenders wat aandui dat die monsters deel is van dieselfde gebeurtenis
Dissertation (M.Sc. (Geology))--University of the Free State, 2010
Keywords: Chondrite; Mineralogy; Geochemistry; Classification; Thuathe; Machinga; Balaka; Chisenga; Asab; Chondrites (Meteorites); Meteorites--Classification; Electron microscoby